The militarization of American professional sports: How the sports-war intertext influences athletic ritual and sports media - Jenkins, T. (Journal of Sport and Social Issues, 2013)
This article investigates how "war-speak" is incorporated into both sports media coverage and athletic rituals. It posits that while the militarization of American sporting events may help to comfort a nation in crisis and afford the Armed Forces a valuable recruitment tool, it simultaneously encourages a coercive patriotism that is morally problematic for many athletes and fans, especially during wartime. Likewise, although the use of war metaphors in sports media coverage provides exciting and dramatic language for players and sportscasters, it also devalues the war experience by trivializing its horrors and helps to sell the concept of war as sport.